Penerapan Metode Logika Fuzzy Mamdani Untuk Mengenali Tingkat Ketergantungan Pada Game Online di Kalangan Pelajar Kabupaten Ende - Dewa, Lidwin Andrin Floren (Universitas Multi Data Palembang, 2024)
Online Game is a game played using hardware such as gadgets, laptops, or PCs online by several people at the same time. According to Databoks, Indonesia itself is the third-largest game industry market out of 10 countries, with a percentage of 94.5% in the age range of 16-64 years as of January 2022. Online games have had a significant impact on students, particularly students in Ende district. This change has triggered negative behaviors in various aspects of life, including health, psychological, academic, and social aspects. This study aims to apply and identify the level of addiction among students to online games using the Fuzzy Mamdani method, which will later be used to develop an expert system to detect the level of online game addiction. The input variables for online game addiction in students consist of playing duration, internal drive, and inability to restrain oneself, while the output variables include non-addicted, addicted, and highly addicted. In the fuzzy inference system, the Mamdani method is one of the methods with high accuracy. The results of this study indicate that the use of the Fuzzy Mamdani method is accurate in measuring the level of online game addiction among students in Ende district. The implementation of the Mamdani method resulted in a score of 36.06, which can be concluded as non-addicted to online games among students in Ende district.